Body Weight, Oocyte Elimination and Blood Profile of Rabbit After Challenge Test Using Eimeria stiedai - Indrasanti, Diana; Indradji, Mohandas; Hastuti, Sri; Fitriyani, Nur; Munawaroh, Sitie; Hikmawati, Nita; Irawan, Desika Indra (ANIMAL PRODUCTION, 2018)
The objective of the research was to investigate body weight, oocyte elimination and blood profile of rabbits infected with various doses of Eimeria stiedai isolates. The observed rabbits’ blood profile included erythrocyte, hemoglobin, hematocrit, leucocyte, thrombocyte, total protein plasma (TPP) and fibrinogen. Twenty-five male New Zealand White rabbits aged 3 months and weighed approximately 2 kg were provided with pellet and boiled drinking water and Eimeria stiedai isolates. The experiment used Completely Randomized Design to analyze 5 treatments with five replicates. The examined variables included D0: Infection 0 (control of infection without challenge test), D1: Infection 101 with challenge test 103, D2: infection 102 with challenge test 103, D3: infection 103 with challenge test 103, D4: infection 0 with challenge test 103 (control of infection). Data were subject to analysis of variance followed by Honestly Significant Difference Test (HSD). Analysis of Variance result showed that there was no significant difference on body weight, oocyte elimination and blood profile including erythrocyte, hemoglobin, hematocrit, leucocyte, thrombocyte, and fibrinogen. However, total protein plasma (TTP) was significantly different at 5% HSD. It can be concluded that challenge test with Eimeria stiedai has not been used as an alternative in increasing rabbits’ body immune against coccidiosis infection.